Pan-Cancer Molecular Characterization of m6A Regulators and Immunogenomic Perspective on the Tumor Microenvironment - Jie Zhu; Jiani Xiao; Min Wang; Daixing Hu (Frontiers in Oncology, 2021)
PurposeN6-methyladenosine (m6A) methylation plays a critical role in diverse biological processes. However, knowledge regarding the constitution of m6A on tumor microenvironment (TME) and tumor-infiltrating lymphocytes (TILs) across cancer types is still lacking. We performed comprehensive immuno-genomic analyses to reveal molecular characterization of the m6A regulators and immune-related genes (IRGs) across TME and TIL heterogeneity.MethodsWe comprehensively analyzed the properties of m6A regulators in genomic profiles from The Cancer Genome Atlas (TCGA) according to expression perturbations of crucial IRGs, CD274, CD8A, GZMA, and PRF1. The four IRGs were proved to be reliable biomarkers of TILs and TME via CIBERSORT and ESTIMATE analyses, and their co-expression relationship was certified by TIMER analysis. Based on their median values, the samples from the pan-cancer tissues (N = 11,057) were classified into eight TME types. The RNA expression levels of 13 m6A regulators were compared across TME subtypes. Single-sample Gene Set Enrichment Analysis (ssGSEA) was also used to classify TME clusters, expression variants of IRGs and m6A regulators were verified among TME clusters. Meanwhile, the correlation between m6A regulators and tumor mutational burden (TMB) were tested. Finally, the impacts of IRGs and TME clusters in clinical characteristics and outcomes were revealed.ResultsCD274, CD8A, GZMA, and PRF1 showed similar TILs’ characteristics, of which the level of T cells CD8 and T cells CD4 memory activated are consistent with the expression levels of the four IRGs and higher immune infiltration. Besides, CD274, CD8A, GZMA, and PRF1 were positively correlated with the stromal score or immune score in almost all 33 tumor types. All of four IRGs showed impact between tumor pathological stages or clinical outcomes. Among TME type I to type IV, m6A regulators’ expression drift changed from high-level to low-level in ESCA, BLCA, HNSC, CESC, BRCA, and GBM. However among TME type V to type VIII, m6A regulators drew a shift from low-level to high-level expression in CESC, BLCA, ESCA, KIRP, HNSC, BRCA, KIRC, COAD, LAML, GBM, and KICH. In ssGSEA analyses, IRGs’ expression levels were elevated with the immune infiltration degree and m6A regulators’ expression level varied among three TIL subgroups. With different TMB levels, expression differences of m6A regulators were observed in BLCA, BRCA, COAD, LGG, LUAD, LUSC, STAD, THCA, and UCEC.ConclusionWe identified four crucial IRGs affecting TILs, TME characteristics and clinical parameters. Expression variants of m6A regulators among the subgroups of TME types and ssGSEA clusters suggested that m6A regulators may be essential factors for phenotypic modifications of IRGs and thus affecting TME characteristics across multiple tumor types.